Interstitial Fibrosis Severity Is Not Independently Associated with Anemia in Biopsy-Proven Primary Glomerulonephritis: A Nationwide Registry Analysis - Cebeci E.; TURGUTALP K.; Ozturk S.; Ozluk Y.; GÖKÇAY BEK S.; ŞUMNU A.; SEYAHİ N.; YAVUZ M.; Piskinpasa S.; AKÇAY Ö. F.; et al. (My University, 2026)
Background and Objectives: Anemia is a frequent complication of chronic kidney disease (CKD), primarily attributed to erythropoietin deficiency. Interstitial fibrosis (IF), which disrupts the renal interstitium where erythropoietin-producing cells reside, may contribute to anemia independent of glomerular filtration rate (GFR). However, data in primary glomerulonephritis (PGN) are limited and conflicting. Materials and Methods: In this nationwide multicenter registry analysis (TSN-GOLD), 2794 adults with biopsy-proven PGN were included. Interstitial fibrosis was graded semi quantitatively (0-3). Anemia was defined according to KDIGO/WHO criteria. Multivariable logistic regression models were constructed to evaluate the independent association between IF severity and anemia, adjusting for age, sex, eGFR, log-transformed proteinuria, hypertension, diabetes mellitus, and biopsy diagnosis. Interaction between IF and eGFR was assessed. A predefined subgroup analysis was performed in patients with preserved renal function (eGFR >= 60 mL/min/1.73 m(2)). Results: Anemia was present in 34.4% of patients. Although moderate-to-severe IF was more frequent among anemic patients (p < 0.001), IF severity was not independently associated with anemia in multivariable analysis (p-trend = 0.72). Female sex and lower eGFR were independently associated with anemia. A statistically significant IF & times;eGFR interaction was observed (p = 0.0029), indicating effect modification across renal function levels. The model demonstrated moderate discrimination (AUC = 0.705). In patients with preserved renal function, IF severity was not associated with anemia. Conclusions: In this large multicenter cohort of PGN patients, interstitial fibrosis severity was not independently associated with anemia after adjustment for renal function and clinical covariates. These findings suggest that the association between interstitial fibrosis and anemia in PGN appears largely mediated by renal functional status rather than fibrosis severity alone.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Tıp Genel & Dahili; Klinik Tıp; Klinik Tıp (Med); Medicine General & Internal; Clinical Medicine; Clinical Medicine (Med); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine